Skeletal Muscle Satellite Cells, Mitochondria, and MicroRNAs: Their Involvement in the Pathogenesis of ALS - Tsitkanou, Stavroula; Della Gatta, Paul A.; Russell, Aaron P. (Frontiers in Physiology, 2016)
Amyotrophic lateral sclerosis (ALS), also known as motor neurone disease (MND), is a fatal motor neurone disorder. It results in progressive degeneration and death of upper and lower motor neurones, protein aggregation, severe muscle atrophy and respiratory insufficiency. Median survival with ALS is between two to five years from the onset of symptoms. ALS manifests as either familial ALS (FALS) ( 10% of cases) or sporadic ALS (SALS), ( 90% of cases). Mutations in the copper/zinc (CuZn) superoxide dismutase (SOD1) gene account for 20% of FALS cases and the mutant SOD1 mouse model has been used extensively to help understand the ALS pathology. As the precise mechanisms causing ALS are not well understood there is presently no cure. Recent evidence suggests that motor neuron degradation may involve a cell non-autonomous phenomenon involving numerous cell types within various tissues. Skeletal muscle is now considered as an important tissue involved in the pathogenesis of ALS by activating a retrograde signalling cascade that degrades motor neurons. Skeletal muscle heath and function are regulated by numerous factors including satellite cells, mitochondria and microRNAs. Studies demonstrate that in ALS these factors show various levels of dysregulation within the skeletal muscle. This review provides an overview of their dysregulation in various ALS models as well as how they may contribute individually and/or synergistically to the ALS pathogenesis.